Caracterização de Aeromonas spp isoladas de amostras de ostras e água por método microbiológico e molecular - Silva, Ana Carolina Miranda De Melo; Nascimento, Daniele Lopes Do; Machado, Rosângela Zacarias [UNESP]; Costa, Francisca Neide (Universidade Federal de Goiás, 2014)
This study aimed to isolate and identify Aeromonas bacteria from samples of oysters and water, by microbiological and molecular methods. Identification of Aeromonas was performed by the conventional method and by PCR and species characterization was performed by identification key Aerokey II and by RFLP-PCR of 16S rDNA. 59 (98.3%) samples of oysters and 15 (75%) samples of water contaminated by Aeromonas bacteria were identified. Of the 74 isolates of Aeromonas spp. obtained by microbiological analysis, 53 (71.62%), 38 (65.51%) oyster samples and 15 (100%) of water samples confirmed the characterization of the genus by molecular technique. As to biochemical species identification, 59.3% (n = 35) and 40.6% (n = 24) of isolates from Aeromonas sp. obtained from oyster samples were rated as A. hydrophila and A. caviae, respectively; and from isolates obtained from water samples, 60% (n = 9) were classified as A. hydrophila and 40% (n = 6) as A. caviae; however, only the A. hydrophila was confirmed by genetic sequencing. Regarding the classification by RFLP-PCR 16S rDNA, patterns of nonspecific bands were obtained, making it impossible to identify the species by this technique. The large number of oyester samples contaminated with Aeromonas spp. and identification of A. hydrophila, demonstrate that this mollusk might present a risk to consumer health, mainly because it is consumed raw and is to a potentially pathogenic micro-organism to humans.

Objetivou-se isolar e identificar bactérias do gênero Aeromonas de amostras de ostras e de água, pelos métodos microbiológico e molecular. A identificação do gênero Aeromonas foi realizada pelo método convencional e pela técnica da PCR e a caracterização das espécies foi realizada pela chave de identificação Aerokey II e pela técnica de RFLP-PCR do 16S rDNA. Foram identificadas 59 (98,3%) amostras de ostras e 15 (75%) amostras de água contaminadas por bactérias do gênero Aeromonas. Dos 74 isolados de Aeromonas spp. obtidos pela análise microbiológica, 53 (71,62%), 38 (65,51%) de amostras de ostras e 15 (100%) de amostras de água, confirmaram a caracterização do gênero pela técnica molecular. Quanto a identificação bioquímica das espécies 59,3% (n=35) e 40,6% (n=24) dos isolados de Aeromonassp. obtidos das amostras de ostras foram classificados como A. hydrophila e A. caviae, respectivamente; e para os isolados obtidos das amostras de água, 60% (n=9) foram classificados como A. hydrophila e 40% (n=6) como A. caviae; entretanto, somente a A. hydrophila foi confirmadapelo sequenciamento genético. Quanto a classificação através da RFLP-PCR 16S rDNA, foram obtidos padrões de bandas inespecíficos, impossibilitando a identificação das espécies por esta técnica. O grande número de amostras de ostras contaminadas com Aeromonas spp. e a identificação da A. hydrophila demonstram que este molusco pode oferecer risco à saúde dos consumidores, principalmente por ser consumido in natura e se tratar de um micro-organismo potencialmente patogênico para o ser humano.
Characterization of Aeromonas spp isolated from water and of oysters samples by microbiological and molecular methods
Keywords: água; Aeromonas; ostras; PCR; Aeromonas; oysters; PCR; water